Foreign Animation Films and the Rising of Anti-Multiculturalism among Parents - Angeningsih, Leslie Retno; Astuti, Nuraini Dwi (Jurnal Komunitas: Research and Learning in Sociology and Anthropology, 2014)
As the impact of globalization, foreign animation films such as Shin Chan from Japan, Krishna from India, Upin-Ipin from Malaysia, Batman and many others from the US are very popular in Indonesia. Those films supposed represent cultures of each nation, so that people can learn multiculturalism. However, those films create inversely. This study aims to know how foreign animation films affect on the rising of anti-multiculturalism among Indonesian parents. Survey is conducted on parents with kindergarten or elementary children in Yogyakarta. The results show that children prefer to watch foreign animation films compare to domestic one. They are more likely to imitate their favorite animation stars by behaving violently, speaking harshly, and disrespectfully to parents.Â  As a result parents tend to blame their children changing behavior on foreign cultures as bad and impolite compare to their own culture. Instead of encouraging better understanding on multiculturalism, foreign animation films has raised anti-multiculturalism among parents.Sebagai dampak globalisasi, film animasi asing seperti Shin Chan dari Jepang, Krishna dari India, Upin Ipin - dari Malaysia, Batman dan banyak lainnya dari Amerika Serikat sangat populer di Indonesia. Film-film seharusnya mewakili budaya masing-masing negara, sehingga orang dapat belajar multikulturalisme. Namun, film-film ini dapat pula berakibat sebaliknya. Penelitian ini bertujuan untuk mengetahui bagaimana film animasi dari luar bisa berpengaruh pada peningkatan anti-multikulturalisme pada orang tua di Indonesia. Survey dilakukan pada orang tua yang memiliki anak TK atau SDÂ  di Yogyakarta. Hasil menunjukkan bahwa anak-anak lebih memilih untuk menonton film animasi asing dibandingkan dengan film dalam negeri. Mereka lebih cenderung untuk meniru bintang animasi favorit mereka dengan berperilaku keras, berbicara kasar, dan tidak hormat kepada orang tua. Akibatnya, orang tua cenderung menyalahkan anak-anak mereka perilaku yang berubah pada budaya asing sebagai buruk dan tidak sopan dibandingkan dengan budaya mereka sendiri. Alih-alih mendorong pemahaman yang lebih baik tentang multikulturalisme, film animasi asing telah meningkatkan anti-multikulturalisme di kalangan orang tua.